Development of X Ray Simulator Learning Media in Junior Aviation Security Course Based on MOOCS - Yuniar, Dwi Candra; Munir, M Syahrul; Febiyanti, Herlina; Anwar, Syaiful (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
The Aviation Security course is a course that must be followed by cadets of the Diploma 3 Airport Management study program. One of the materials in the Aviation security course is Operation of security equipment which contains aviation security equipment, namely X Ray machines. An X Ray machine is a tool used by aviation security personnel to check passengers' belongings. To achieve learning objectives, varied and independent learning resources are needed that are not limited in time and place. This research is motivated by the difficulty of cadets in understanding the material in the package book and the electronic media used is still limited to power point slides. Then to be able to find out the feasibility, response of cadets, educators and lecturers, as well as the effectiveness of MOOCS learning media will be carried out in this study. This research method uses a research and development (R&D) approach which is then adjusted to the needs of researchers, research methods used to produce certain products, and tests the effectiveness of these products. Researchers conduct research first to collect the required amount of data then develop the system and conduct testing and evaluation of the system created. This research was conducted at the Politeknik Penerbangan Palembang from April 2022 to October 2022.